The tax-free exchange loophole : how real investors can profit from the 1031 exchange - Cummings, Jack, 1940- (John Wiley & Sons, 2005)
Discover the Greatest Investment Tool of All Time!The tax breaks and loopholes built into real estate make it one of the most profitable investments in the world. In fact, the real estate tax exchange loophole--known as the 1031 Exchange--is one of the greatest tax loopholes in existence. This loophole allows a real estate investor to sell a property without paying a penny in capital gains tax--as long as the investor reinvests his or her profits into another property. Not only is this a great way to invest without paying taxes, it's also a great way to grow real wealth over time. The.